Post a New Question

Math

posted by on .

Raise the quantity in parentheses to the indicated exponent, and simplify the resulting expression. Express answers with positive exponents (-33xy^-1/66x^0y^-3)^2

This is the answer i am getting from TRYING to follow my online book. Please Help Me. Thank You!
-33/66*x^-3/y^-1y^-3
-3*y^3/x^-1=3y^3/x^3

  • Math - ,

    I would rethink this. Lets do it in parts:
    whole numbers( -33/66)^2= (-1/2)^2= 1/4
    x values (x/x^0)^2= x^2
    y values (y^-1/Y-3)^2=(y^3-1)^2= y^4

    overall: x^2 * y^4 /4

  • Math - ,

    Thanks for your help. I wasn't even using the ^2 outside the parenthesis. Thank YOu!
    Ashley

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question